2020
DOI: 10.1155/2020/7317648
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Colony of Phlebotomus argentipes under Laboratory Conditions and Morphometric Variation between Wild-Caught and Laboratory-Reared Populations

Abstract: The field-based studies on sand flies are not adequate to uncover information required for the control of the leishmaniasis through reduction of vector populations. Therefore, establishment and maintenance of laboratory colonies of sand flies is an essential step in leishmaniasis research. In the current study, a colony of P. argentipes was established from wild-caught sand flies following standard procedures from the published literature. Morphological measurements of laboratory-reared and wild-caught individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Before pupation, fourth instar larvae empty their guts thus making them opaquer and by this time they had not been fed. However, Wijerathna et al (2020) showed that the larval durations of the first, second, third and fourth instars were 5-7, 4-5, 3-4, and 6-9 days respectively while the pupal duration was 8-10 days. The duration of the life cycle, egg hatching, and Biology of P. argentipes 123 larval development in the current study show a contrasting result with that of the study conducted by Wijerathna et al (2020).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Before pupation, fourth instar larvae empty their guts thus making them opaquer and by this time they had not been fed. However, Wijerathna et al (2020) showed that the larval durations of the first, second, third and fourth instars were 5-7, 4-5, 3-4, and 6-9 days respectively while the pupal duration was 8-10 days. The duration of the life cycle, egg hatching, and Biology of P. argentipes 123 larval development in the current study show a contrasting result with that of the study conducted by Wijerathna et al (2020).…”
Section: Resultsmentioning
confidence: 93%
“…However, Wijerathna et al (2020) showed that the larval durations of the first, second, third and fourth instars were 5-7, 4-5, 3-4, and 6-9 days respectively while the pupal duration was 8-10 days. The duration of the life cycle, egg hatching, and Biology of P. argentipes 123 larval development in the current study show a contrasting result with that of the study conducted by Wijerathna et al (2020). This may be because the current study tried to concentrate more on giving natural conditions in the laboratory than using artificial conditions.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…erefore, all the existing data suggest that P. argentipes is potentially competent vector for the transmission of L. donovani. e next steps should be the confirmation of luxuriant growth of the parasite within the CTTTTGATAATCGATATTTGTTTTAAACTGGGTTAGTTCGGCTGGATACACg t t g g t t g g CTTTTGATAATCGATATTTGTTTTAAACTGGGTTAGTTCGGCTGGATGCACGTTGGTTGG a t t g g a t t t g g a t t g g a t t t g g a t t t t a t a c g g g g t t g g g g g c t t g a t t t g g g t sand fly stomdeal valve in the midgut and experimental transmission by vectors under laboratory conditions [42,46]. e use of retrospective data to generate mathematical modeling-based proof of this species being essential for the maintenance of the parasitic transmission cycle with or without the involvement of other vectors is also a necessity.…”
Section: Discussionmentioning
confidence: 99%